Inflammation in parkinson's disease : scientific and clinical aspects - Thomas, Madhavi (Springer International Publishing, 2014)
Inflammation in Parkinson's Disease brings advances in research together with current literature and evidence.  This concise volume covers the fundamentals of neuroimmunology and inflammatory models, the interactions between pathways of neurodegeneration and follows the concept of research work undertaken from basic science to clinical trials.  Researchers, clinicians, and students interested in Parkinson's Disease are provided with a comprehensive view of translational research methods and an insight needed for developing future therapies aimed at disease modulation.